2016
DOI: 10.1016/j.molcel.2016.05.033
|View full text |Cite
|
Sign up to set email alerts
|

eIF3 Peripheral Subunits Rearrangement after mRNA Binding and Start-Codon Recognition

Abstract: mRNA translation initiation in eukaryotes requires the cooperation of a dozen eukaryotic initiation factors (eIFs) forming several complexes, which leads to mRNA attachment to the small ribosomal 40S subunit, mRNA scanning for start codon, and accommodation of initiator tRNA at the 40S P site. eIF3, composed of 13 subunits, 8 core (a, c, e, f, h, l, k, and m) and 5 peripheral (b, d, g, i, and j), plays a central role during this process. Here we report a cryo-electron microscopy structure of a mammalian 48S in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
161
3
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(173 citation statements)
references
References 62 publications
(112 reference statements)
8
161
3
1
Order By: Relevance
“…Recent studies reveal structural rearrangements within 43S/48S PICs between different steps of initiation (Hussain et al, 2014; Llacer et al, 2015; Simonetti et al, 2016). However, it is unclear exactly how start codon selection induces transition from the open to closed conformations of the PIC.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies reveal structural rearrangements within 43S/48S PICs between different steps of initiation (Hussain et al, 2014; Llacer et al, 2015; Simonetti et al, 2016). However, it is unclear exactly how start codon selection induces transition from the open to closed conformations of the PIC.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report located mammalian eIF3i to a distinct location on the intersubunit face and suggested that the eIF3b β-propeller instead interacts with TC in the yeast 48S PIC (Simonetti et al, 2016). While this model would not explain the TC binding defects we observe in the absence of eIF3i and eIF3g, it would nonetheless still be consistent with the defects in TC affinity that we observe in the presence of eIF3b mutants and with a role for the eIF3 entry channel arm in stabilizing TC binding to the PIC.…”
Section: Discussionmentioning
confidence: 99%
“…In this structure, the eIF3i (maroon) and eIF3g (red) subunits are located together with the eIF3b C-terminal region on the intersubunit face near the A site and below the intersubunit-face opening of the mRNA entry channel, where eIF3i interacts with the eIF2γ portion of the TC (green and charcoal). In a recent structure of mammalian eIF3 bound to an apparently late-stage initiation complex, eIF3i was found at a distinct location on the intersubunit face of the PIC, leading to the suggestion that the density observed near TC in the yeast py48S-closed structure is in fact the β-propeller of eIF3b and not eIF3i (Simonetti et al, 2016).
10.7554/eLife.20934.003Figure 1.A library of S. cerevisiae eIF3 functional variants affected by mutations spanning all five essential subunits.Three views of the cryo-EM structure of eIF3 bound to the partial yeast 48S PIC in the closed conformation (py48S-closed), as reported by Llacer, et al .
…”
Section: Introductionmentioning
confidence: 99%
“…This implies that eIF5 would make only secondary contacts with the 40S subunit and therefore be relatively disordered with respect to it. The eIF3big complex has been weakly resolved in contact with eIF2 on the subunit interface in the presence of mRNA, a position that is considerably different compared with its position on the 40S solvent-exposed surface in complexes in the absence of mRNA, suggesting a conformational change during scanning [9,21]. While there is currently no mechanistic explanation for this observation, it appears plausible that might be involved in the communication of the stable incorporation of the ternary complex and mRNA to other factors bound by the scaffold ( figure 3). rstb.royalsocietypublishing.org Phil.…”
Section: Start-codon Selection: To Stay or To Gomentioning
confidence: 99%